Teaching Development with SIM-MOM Simulation in Maternal and Child Nursing and Midwifery Practicum 2 Student Nurses of Saint Louis College - Sirilukkananan, Kaewtawan; Kruachottikul, Supawadee; Poomsrikaew, Sirilak (NU Journal of Nursing and Health Sciences, 2022)
This research was aimed to 1) study the results of learning management with SIM-MOM simulation in maternal and child nursing and midwifery practicum 2 and 2) to compare the commitment, capacity, confidence, compassion and complacency of nursing students studying through the SIM-MOM simulation prior to the ward practice and those practicing on the ward before learning using the SIM-MOM simulation. Samples comprised 70 nursing students who studied the Maternal and Newborn Nursing & Midwifery Practicum II subject in the 2nd semester of academic year 2019 divided into 35 students studying through the SIM-MOM simulation prior to the ward practice and 35 students practicing on the ward before learning using the SIM-MOM simulation using simple random sampling. Research tools included SIM-MOM models, questionnaires on learning outcomes of nursing students and group discussion. Statistics used for the research included percent, mean, standard deviation, the t-test and content analysis of group discussion. The results of the research revealed that the mean scores of commitment, confidence, compassion, capacity and complacency of both sample groups were high. The difference in means scores of confidence and capacity of both groups was statistically significant at .05 level. However, other mean scores were not different. Research recommendations suggested that the teaching team should organize a workshop to jointly develop a diversity of simulation scenarios to be easy or difficult to match each subject, help increase learners’ skills and knowledge, select teaching methods and organize activities that suit the content of the subject and what needs to be enhanced or developed, as well as take into consideration the context of nursing students. In addition, the SIM-MOM simulation model should be reviewed prior to the students’ practice in higher year level.